The joining of the stone - Murphy, Shirley Rousseau (Atheneum, 1981)
Lobon, son of Ramad of the Wolves, helped by the wolves and the Seers of Carriol, continues his father's struggle to find the shards of the runestone and unite them for the power of good. Sequel to "Caves of Fire and Ice."